Levetiracetam induced drug reaction with eosinophilia and systemic symptom syndrome - Waseem Raja Dar; Najeebullah Sofi; Muzamil Latief; Imtiyaz Ahmad Dar; Basharat Ahmad Kasana (Wolters Kluwer Medknow Publications, 2016)
Drug reaction with eosinophilia and systemic symptom syndrome (DRESS) is a hypersensitivity drug reaction, most frequently associated with antiepileptic drugs, characterized by skin rash, fever, pharyngitis, lymphadenopathy, and visceral organ involvement, typically presenting within 8 weeks of initiation of therapy. Management involves prompt withdrawal of the offending drug and use of systemic corticosteroids. We here present a rare case of DRESS secondary to levetiracetam. Only few case reports of DRESS secondary to levetiracetam have been published so far.